2010
DOI: 10.1007/s00134-010-1818-4
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of C-reactive protein, procalcitonin, and mid-regional pro-atrial natriuretic peptide to guide site of care of community-acquired pneumonia

Abstract: In a selected population of CAP with low risk of complication, a single ANP measurement was more accurate than CRP and PCT to predict appropriate admission. These results should be confirmed by additional studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 49 publications
3
16
0
2
Order By: Relevance
“…On the contrary, in a study by Hohenthal et al, CRP correlated significantly with the PSI and was valuable for assessing disease severity [36]. Our results confirm previous findings that have shown that MR-proANP correlates with PSI, CURB-65, the later development of complications, and the length of hospitalization [16,37,38,44,45]. MR-proANP is involved in physiopathological changes that occur during infections, and this is one of the reasons why its levels are increased in patients with CAP.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On the contrary, in a study by Hohenthal et al, CRP correlated significantly with the PSI and was valuable for assessing disease severity [36]. Our results confirm previous findings that have shown that MR-proANP correlates with PSI, CURB-65, the later development of complications, and the length of hospitalization [16,37,38,44,45]. MR-proANP is involved in physiopathological changes that occur during infections, and this is one of the reasons why its levels are increased in patients with CAP.…”
Section: Discussionsupporting
confidence: 89%
“…MR-proANP is involved in physiopathological changes that occur during infections, and this is one of the reasons why its levels are increased in patients with CAP. The proposed cut-off for the prediction of complications and mortality is similar to those reported in previous studies [16,44].…”
Section: Discussionmentioning
confidence: 83%
“…There is a strong correlation between MR-proANP and pneumonia clinical scores (PSI, CURB65 and CRB65) [44,45,60,61] and it predicts hospital admission better than CRB65, CRP or PCT [62]. Moreover, it is also a superior prognostic indicator for short-and long-term mortality [44,61] than clinical scores (PSI or CRB65) or other biomarkers like PCT or CRP [63,64].…”
Section: Biomarkersmentioning
confidence: 95%
“…A systematic review of 12 studies confirms that an increased MR proADM is associated with increased risk of short term mortality and that a combination of proADM and CURB-65 is associated with an improved predictive efficacy (90). A sizable Swiss study discovered that ProADM was strong predictor of TF including death with an AUC that was significantly higher than that of CRP but similar to PCT (91)(92)(93). Similarly Copeptin has been shown to be a useful marker of early mortality or ICU admission, more so than other biomarkers (89).…”
Section: Novel Biomarkersmentioning
confidence: 89%